Fish as bioindicators for waiting period of pesticides - Chatterjee, Amita; Adhikari, S; Adhikari, S P; Ayyappan, S (Indian Journal of Fisheries, 2011)
Experiments were conducted in semi-pond as well as aqueous media with glyphosate, butachlor and cypermethrin for their waiting period and degradation studies using the survivabilities of Labeo rohita, Channa punctatus, Anabas testudineus and Heteropneustes fossilis as bio-indicators. The results showed that the waiting period of glyphosate, butachlor and cypermethrin existed in between 13 and 18 days; 91 and 120 days and 7 and 10 days, respectively, in semi-pond conditions. The degradation of pesticides as measured by fish survivability percentage indicated that though in case of glyphosate, a period of 18 days showed 100 percent fish survivability both in semi-pond and aqueous media, in case of cypermethrin and butachlor, there was a difference of about seven days and 20 days respectively, in between semi-pond system and only aqueous system to achieve 100 percent fish survivability which demonstrated that soil in the semi-pond system could play a vital role in pesticide degradation. Moreover, in glyphosate-treated water, 0.721 mg/l more dissolved phosphorus was recorded after 12 days, while in butachlor-treated water, 0.596 mg/l more dissolved nitrogen was observed after 90 days and in cypermethrin-treated water, 0.340 mg/l more dissolved nitrogen was recorded after seven days as compared to control.